Platelet rich fibrin as a sole grafting material For the treatment of periodontal Intrabony defects. - Dr. POOJA M. PHARNE; Dr. DILIP B. MAGDUM; Dr. SUVARNA T. JADHAV; MRS. PATIL SMITA V. (International Journal of Pharma and Bio Sciences, 2016)
Platelet-rich fibrin (PRF) is a second-generation platelet concentrate enriched with platelets and growth factors which found to be beneficial for periodontal regeneration. The purpose of this case report is to clinically and radiographically evaluate the efficacy of PRF for the treatment of periodontal intrabony defects (IBD). A 38- year old Indian female presented with periodontal IBD in relation to 21. The probing pocket depth (PPD), clinical attachment level (CAL) and Mean bone defect were found to be 13mm,14mm and 17.30 mm respectively in relation to 21. The affected lesion was treated surgically by placement of PRF which showed significant reduction in PPD, gain in CAL and radiographic bone formation after six months, thus supporting the role of various growth factors present in the PRF in accelerating the soft and hard tissue healing.